Penggunaan Minyak Kelapa Mandar sebagai Agen Alternatif Deparafinisasi pada Pewarnaan Rutin Hematoksilin-Eosin - Putri, Gela Setya Ayu; Zalzabillah, Nurul Fhatiah (Poltekkes Kemenkes Semarang, 2025)
The deparaffinization technique is critical in hematoxylin-eosin staining tissue slides. Xylol is an organic solvent that is frequently used as a deparaffinization agent, however, it has several hazardous effects. Alternative deparaffinization agents that are safer for the environment and humans are required, one of which is traditional mandar coconut oil (MTM). Lauric acid in MTM is non-polar, hence it can dissolve paraffin. The study aimed to evaluate the quality of staining results in mouse liver slide during the deparaffinization process using xylol and MTM with Hematoxylin-eosin (HE) staining. This study is an experimental design that uses 40 samples of mouse liver tissue slides, which were divided into two treatment groups. The Man-Whitney test was used to analyze data on the quality of tissue staining results based on nucleus, cytoplasm, and color homogeneity. The results of the staining quality of the mouse liver slide in the xylol and MTM groups obtained 100% good (score 3). The conclusion in this study is traditional mandar coconut oil (MTM) is effective for use as an alternative deparaffinization agent in HE staining.